Injectable formulation of a novel anti-breast cancer drug. - Wei, Na. (2012)
Acetyltanshinone IIA (ATA), a novel discovered anti-breast drug, is chemically modified from Tanshinone IIA with low aqueous solubility and bioavailability which is isolated from the dry root of the Chinese herbal Danshen. After specific chemical conformational modifications, ATA has many advantages over tanshinone IIA, such as improvement of apoptosis effects against breast cancer, especially ER positive and HER2 positive breast cancer cells. So as for animal experimental study and clinical trials, the injectable formulation should be given the priority in drug development owing to its effective enhancement of drug bioavailability and permission of rapid entrance into the blood. In this study, mainly two approaches were employed to improve the solubility and dissolution rate of ATA, including multiple co-solvents and surfactants and nanosuspension. Dissolving drugs into multiple co-solvents and surfactants is the first step in the development of drug formulations. Encapsulating drugs by PLGA nanoparticles which has been widely applied in controlling of drug release and targeting in the drug delivery will become another feasible approach to investigate ATA injectable formulation.